Evaluasi Invisible Lost Time dan Non-Productive Time Pada Sumur X Menggunakan Data End Of Well - Edy Soesanto; Assyeh Annassrul Majid (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
One of the characteristics of the oil and gas sector, especially drilling activities, is High Cost, namely high operational costs. Therefore, efficient and effective use of time is necessary to reduce operational costs. Evaluation of the influence of ILT and NPT on drilling activities was carried out to find the factors that made drilling time so long. Identifying KPIs for each activity is necessary to find out what activities can be optimized. From the analysis results it was found that the Invisible Lost Time value was 33.12% (198.75 hours) and Non-Productive Time was 18.37% (110.25 hours) caused by less than optimal performance and equipment failure. The author believes that the factors causing the relatively high ILT and NPT can still be optimized so that the costs required during drilling activities are in accordance with the desired planning.